Optimalisasi Usaha Petambak Melalui Pengembangan Umkm Kerupuk Lele Di Desa Sukamandi - Harista, Eva (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
One of the community service programs carried out by KKN Group 36 students in Suka Mandi Village, East Belitung Regency is to advance UMKM through the manufacture of catfish crackers. This community service method uses PAR (Participatory Action Reaseach). PAR is a research-based service method carried out by the community in the community environment as participants who are actively involved in service activities. PAR has three components, which consist of: research methodology, action, and participation. The main activities include training in catfish cracker making and product socialization to the local community, as well as analysis of constraints faced such as processing and marketing skills. The findings and results of this activity show that the community has gained basic knowledge about the process of making catfish crackers, but still has difficulties in aspects of technical skills and marketing strategies. To improve the effectiveness of the program, additional training, development of more effective marketing strategies, and establishing partnerships with distributors are recommended. These steps are expected to accelerate the development of catfish cracker UMKM and contribute more to the local economy.